Overcoming therapeutic resistance to platinum-based drugs by targeting Epithelial–Mesenchymal transition - Duan, Xirui; Luo, Maochao; Li, Jian; Shen, Zhisen; Xie, Ke (Frontiers in Oncology, 2022)
Platinum-based drugs (PBDs), including cisplatin, carboplatin, and oxaliplatin, have been widely used in clinical practice as mainstay treatments for various types of cancer. Although there is firm evidence of notable achievements with PBDs in the management of cancers, the acquisition of resistance to these agents is still a major challenge to efforts at cure. The introduction of the epithelial-mesenchymal transition (EMT) concept, a critical process during embryonic morphogenesis and carcinoma progression, has offered a mechanistic explanation for the phenotypic switch of cancer cells upon PBD exposure. Accumulating evidence has suggested that carcinoma cells can enter a resistant state via induction of the EMT. In this review, we discussed the underlying mechanism of PBD-induced EMT and the current understanding of its role in cancer drug resistance, with emphasis on how this novel knowledge can be exploited to overcome PBD resistance via EMT-targeted compounds, especially those under clinical trials.